Effect of selective vaccination on rubella susceptibility and infection in pregnancy. Issue 6506 (16th November 1985) - Miller, C L; Miller, E; Sequeira, P J; Cradock-Watson, J E; Longson, M; Wiseberg, E C
Abstract : The effect of school and adult vaccination on susceptibility to rubella in women of childbearing age was assessed in the Manchester area, where the population attending antenatal clinics is over 40 000 a year. Between 1979 and 1984 the proportion susceptible fell from 6.4% to 2.7%. In 1984, 4.2% of nulliparous women were susceptible compared with 1.4% of women in their second or subsequent pregnancy. Eighty five per cent of pregnant women screened and found to be non-immune were vaccinated post partum before leaving hospital. Requests for prevaccination screening of non-pregnant women increased in response to a national campaign and at the time of local outbreaks of rubella but only two thirds of those found to be nonimmune were subsequently vaccinated. During 1983 and 1984 infection was confirmed in 57 pregnant women–2% of those non-immune. Selective vaccination has reduced susceptibility to rubella in the childbearing population, but it is suggested that mass vaccination of children of both sexes should be added to the existing policy to control circulation of wild rubella virus and reduce the risk of infection to pregnant women who remain susceptible.